The Relationship Between the Level Fabp4, Risks of Type 2 Diabetes Mellitus, and Cardiovascular Events - Laryushina, Yelena; Parakhina, Viktoriya; Turmukhambetova, Anar; Turgunova, Lyudmila; Ibraeva, Lyazat; Amirkhanova, Dana; Nildibayeva, Farida (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The normoglycemic patients with diabetes risk and prediabetes have insulin resistance and consequently endothelial dysfunction that possible causes macroangiopathy and adverse cardiovascular events and further mortality of it. An early diabetes risk identification using not only prognostic scales but also biomarkers is starting and crucial point of struggle with 2 type diabetes mellitus and its complications. AIM: The aim of the study is to estimate the impact of FABP4 biomarker on diabetes risk and cardiovascular events. METHODS: A cross-sectional study was conducted simultaneously among 389 respondents aged 18–65 years. We provided survey and clinical examinations. The risk of diabetes was assessed using the FINDRISC scale and cardiovascular risk (CVR) was assessed using SCORE scale. The serum FABP4 biomarker was studied using a multiplex assay, immunofluorescence using XMap technology, a Bioplex 3D instrument, and a MILLIPLEX® Human cardiovascular disease panel I reagent kit(Millipore). Results were considered statistically significant at p < 0.001. RESULTS: The group of type 2 diabetes mellitus (T2DM) high risk was 79 (20%) of all study participants. The level of the FABP4 marker significantly prevailed in high-risk group of T2DM and high CVR was also established this group. We found a positive direct average correlation(r = 0.59; p = 0.000) between FABP4 and FINDRISC scale. The logistic regression analysis indicated that the level of the FABP4 marker increases withing the increased risk of T2DM. The correlation between FABP4 concentration and CVR according to the SCORE scale (r = 0.24; p = 0,000) was lower than between FABP4 and diabetes risk. Risk factors were established affecting on the increasing CVR by SCORE scale in patients with T2DM risk. CONCLUSIONS: The level of FABP4 significantly prevailed in the group of diabetes and cardiovascular risk (CVR). The established correlations between FABP4 level and CVR or T2DM risk indicate on its increase in groups with a higher risk of type 2 diabetes and a high CVR.